Testicular Torsion and Epididymitis Demonstrated by Radionuclide Angiograms and Static Imaging - Hankins, Andrew J. (1979)
Radionuclide testicular angiography and static images were performed using technetium 99m sodium pertechnetate in an effort to differentiate between testicular torsion and acute epididymitis in 12 patients. The diagnosis of testicular torsion was made in four cases that were confirmed at surgery. Acute epididymitis or acute epididymo-orchitis was diagnosed six times. These patients were treated with broad-spectrum antibiotics leading to a subsidence of their clinical symptomatology during therapy with no sequelae. The radionuclide angiogram and static image changes of chronic epididymitis are also discussed. Radionuclide testicular angiograms and static images can be significant benefits in addition to the clinical and physical findings to distinguish between testicular torsion and acute and chronic epididymitis.